ANALISIS KEKERINGAN METEOROLOGI DENGAN MENGGUNAKAN METODE STANDARDIZED PRECIPITATION INDEX DI KUPANG – NUSA TENGGARA TIMUR - Krisnayanti, Denik Sri; Pasoa, Mirnawati S; Cornelis, Remigildus (JURNAL SUMBER DAYA AIR, 2023)
Kupang City and Kupang Regency have semiarid climatological conditions where annual rainfall ranges from an average of 1,250 mm/year. Kupang City and Kupang Regency experience long days without rain, which potentially causes meteorological drought. The study aims to determine the value and distribution of the drought index in Kupang City and Kupang Regency. This study uses the Standardized Precipitation Index (SPI) method using rainfall data for 21 years (1998-2018) from 12 rainfall stations, while the mapping uses ArcGIS Software. The results obtained from this study are the extreme level of drought in Kupang Regency and Kupang City occurred in 2015-2016. A 1-month SPI Kupang City experienced the highest drought in January 2004 at -3.48, while Kupang Regency occurred in November 2015 at -3.06.  The 3-month SPI Kupang City experienced the highest drought in January 2016 at -3.85, while Kupang Regency occurred in December 2012 at -4.13. The 6-month SPI of  Kupang City experienced the highest drought in January 2016 at -4.04, while Kupang Regency occurred in November 2015 at -4.82.  The 12-month SPI Kupang City experienced the highest drought in March 2016 at -3.76, while Kupang Regency occurred in April 2016 at -3.36. The 6-month SPI tends to fluctuate more in value than the 1-month SPI, 3-month SPI, and 12-month SPI. The drought years that occurred in 2015 – 2016 triggered forest and land fires in Kupang City. Besides that,  the Meteorological drought must be anticipated by setting appropriate cropping patterns to avoid food insecurity. Keywords: Drought, semiarid, land fires, mapping